Effective magnetization damping for a dynamical spin texture in metallic ferromagnet - Sukhostavets, O.V.; Gonzalez, J.M.; Guslienko, K.Y. (Физика низких температур, 2015)
An additional magnetization damping for an inhomogeneous spin texture in metallic ferromagnets is calculated
on the basis of the s–d exchange model. The effect of conduction electrons on the magnetization dynamics is
accounted for the case of slowly varying spin texture within adiabatic approximation by using a coordinate transformation
to the local quantization axis. The moving magnetic vortex in a circular nanodot made of permalloy is
considered as an example. The dependence of the damping on the dot geometrical sizes is obtained. It is found
that the additional damping can reach up to 50% of magnitude of the phenomenological Gilbert damping in the
Landau–Lifshitz equation of magnetization motion and should be taken into account for any inhomogeneous
spin texture dynamics in ferromagnetic metals.